Principal feature determination in textured image - Tang, Lai Meng. (2009)
Texture analysis has been an active research area in computer vision for more than two decades, and has proved to be a very difficult problem. This difficulty largely stems from the diversity of natural and artificial textures, which makes a universal definition of texture impossible. Compared to other approaches, the multi-channel filtering approach to texture analysis is more general and applies to a larger class of textures. This generality is a direct consequence of reliance on the basic attributes of frequency and orientation, and the inherent multi-resolution nature of the approach.